La luce e l’origine del tempo vissuto - Gatti, Maria Gabriella (Il sogno della farfalla, 2015)
The article presents an overview of the most recent literature on the non-visual aspects of luminous stimulation on the human brain. The main processes involved in them and their importance for the beginning of human life have only been clarified recently. The author discusses the significant convergence between the most up-to-date biological research and the “Birth Theory” by Massimo Fagioli, an author who more than 40 years ago described the determining role of light in the origin of psychic activity as it impacts on brain matter and gives rise to human mental activity, inner movement and “lived” time.